KAJIAN ANALISIS TRANSPOR SEDIMEN DI LOLASI RENCANA PELABUHAN KAWASAN INDUSTRI BANTAENG - Bulawan, Chofifah Datu; Paotonan, Chairul; Umar, Hasdinar (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Bantaeng Industrial Zone (KIBA) is located in Bantaeng Regency and was initiated with the establishment of Bantaeng Regional Regulation Number 2 of 2012 concerning the Spatial Planning of Bantaeng Regency for the period 2012-2032. The Pa'jukukang Subdistrict was designated as a large industrial area covering an area of 3,128 hectares. KIBA was also designated as a National Strategic Project (PSN) through Presidential Regulation 9 of 2022 regarding the Amendment to Presidential Regulation 7/2021 on the Amendment of the National Strategic Project List. Based on data from the Bantaeng Regency Investment and One-Stop Service Office from 2010 to 2017, there were 13 companies with various business fields. Changes in the coastline along the Bantaeng coast are caused by sediment transport resulting from wind and wave action. This study aims to determine the characteristics of sediment and the annual sediment transport rate along the coast. The sediment transport analysis results indicate that for the representative 1% wave, it is 2,134.84 m3/year, for the representative 10% wave, it is 993.91 m3/year, for the representative 50% wave, it is 461.45 m3/year, and for the representative 100% wave, it is 147.89 m3/year. All sediment transport is directed westward. The larger the percentage of the representative wave, the smaller the total sediment transport discharge (Q) produced.